Romeo and Juliet [videorecording] - Luhrmann, Baz.; Martinelli, Gabriella ([S.l.] Bookmark Production, 1996)
Baz Luhrmann's adaptation of William Shakespeare's classic love story. A retelling of the world's most tragic love affair. But the setting has been moved from its Elizabethan origin to the futuristic urban backdrop of Verona Beach.
Baz Luhrmann's adaptation of William Shakespeare's Rome and Juliet.
VHS.
Credits : Screenplay by Craig Pearce, Baz Luhrmann.
Leonardo de Caprio as Romeo ; Claire Danes as Juliet.
Keywords: Shakespeare, William -- 1564-1616 -- Adaptations; Feature films